Academic Freedom of Expression in Indonesia: A Maqashid Sharia Notes - Al-Fatih, Sholahuddin; Aditya, Zaka Firma; Fuadi, Abdul Basid; Nur, Muhammad (El-Mashlahah, 2023)
This article intended to examine academic freedom in Indonesia, especially in the last decade (2014-2022). As a country that upholds human rights and Islamic values, academic freedom in Indonesia is in chaos, especially on hifz al-nafs and hifz al-‘aql fulfillment. Many forms of thought expression and criticism conveyed by scholars to the government in academic forums are responded to with various terror, threats, and criminalization on the grounds of state stability. Scholars who are critical of government policies fall victim to criminalization, go to prison, and are dismissed from college due to being considered to violate college ethics. The many cases of academic freedom infringement indicate a severe problem where the thought of scientists in an academic forum is being ‘undermined